Relationship Between Visual Constructive Abilities and Activity of Daily Living in Home Dwelling Elderly Population - Negin Chehrehnegar; Fariba Keshavarzi; Negar Rahnamaee; Zahra Aghajafari (University of Social Welfare & Rehabilitation Sciences, 2016)
Objectives: Increasing life expectancy and decreasing birthrates have significantly contributed to an increased aging population throughout the world. This sudden change is a global phenomenon often resulting in biological changes that may have various consequences, such as reduced life power and coping skills in the elderly population. Cognitive deficits are one of the most severe impairments in the elderly people. Deficits in cognitive abilities, especially visual constructive skills, can have a considerable impact on the independency of the daily living skills of the elderly people. Self-care by individuals to maintain their life and wellbeing is a key element for their independency. The activity of daily living (ADL) can support personal life independency, and is considered as a morbidity index. In the present cross-sectional study, we assessed the visual abilities and ADL in older subjects to determine whether cognitive impairment is associated with changes in self-care behavior. Methods & Materials: This study employed random sampling technique to select and recruit forty seven individuals aged between 60 to 80 years from Jahandidegan club in Shiraz, Iran. They were evaluated through "visual constructive ability" sub-scale from Loewenstein Occupational Therapy Cognitive Assessment (LOTCA) battery and "Katz Index", which were used to assess their associated skill and ADL, respectively. Data was collected through observation and interviews. Data analysis was performed through Pearson's correlation test using SPSS. Results: The mean age of the participants (9 women and 38 men) was 69.94±4.66 years. Lower scores in cognitive domains predicted functional decline in some scales. There was a significant correlation between visual constructive ability and eating; however, no significant correlation was found between this sub-scale with bathing, moving, toileting, and bowel control. Conclusion: In summary, a significant correlation was noted between visual constructive abilities and dressing and eating activities. A weak correlation was observed between cognition and personal independency that may result from the less demanding cognitive processing tasks.